2020
DOI: 10.1111/sms.13883
|View full text |Cite
|
Sign up to set email alerts
|

Massage enhances recovery following exercise‐induced muscle damage in older adults

Abstract: To examine efficacy of cold water immersion (CWI) and massage as recovery techniques on joint position sense, balance, and fear of falling following exercise‐induced muscle damage in older adults. Seventy‐eight older men and women performed a single bout of strength training on the calf muscles (3 exercises with 4 sets of 10 reps with 75% of 1RM) to induce muscle damage. After the damaging exercise, participants received either a 15‐minute massage on calf muscles, or a CWI of the lower limb in cold water (15 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Studies that assessed function of the elbow flexors tended to report larger decreases in strength than those that assessed function of the lower limbs. For example, decreases in elbow flexor MVC after exercise ranged from 42 to 49% [47,51], whilst decreases in plantar flexor and knee extensor strength ranged from 9 to 36% [54,55]. Of the four studies that measured elbow flexor strength [45][46][47]51], three were conducted by the same research group using the same exercise protocol [45][46][47].…”
Section: Symptoms Of Exercise-induced Muscle Damage Physical Functionmentioning
confidence: 99%
“…Studies that assessed function of the elbow flexors tended to report larger decreases in strength than those that assessed function of the lower limbs. For example, decreases in elbow flexor MVC after exercise ranged from 42 to 49% [47,51], whilst decreases in plantar flexor and knee extensor strength ranged from 9 to 36% [54,55]. Of the four studies that measured elbow flexor strength [45][46][47]51], three were conducted by the same research group using the same exercise protocol [45][46][47].…”
Section: Symptoms Of Exercise-induced Muscle Damage Physical Functionmentioning
confidence: 99%
“…Components of multimodal chiropractic care such as soft tissue massage, prescriptive exercise, and kinesiology taping have shown mixed effectiveness in enhancing proprioception. Older adults who received massage following exercise saw benefit in measures of joint position sense [ 115 ] and changes in plantar sensation have been observed following the use of plantar massage [ 116 ]. The use of prescriptive exercise for the direct purpose of improving proprioceptive functioning is supported by one study showing improvement with lumbopelvic motor control exercise [ 117 ] but countered by another showing no changes following tactile acuity training [ 118 ].…”
Section: Main Textmentioning
confidence: 99%
“…By contrast, CWI following eccentric contractions did not affect muscle soreness or strength in humans . More recently, Naderi et al showed that CWI did not attenuate a loss in muscle strength following a single bout of strength training (Naderi et al, 2021), whereas Kodejška et al (2018) demonstrated that CWI increased the force time integral in handgrip performance compared with passive recovery in rock climbers. Differences in CWI study outcomes could be associated with different modes of exercise, methods or timing of applying CWI and approaches to assessing muscle damage.…”
Section: A Brief History Of Cwi Researchmentioning
confidence: 99%